2013
DOI: 10.3109/14767058.2013.860520
|View full text |Cite
|
Sign up to set email alerts
|

A familial case of Muenke syndrome. Diverse expressivity of theFGFR3Pro252Arg mutation – case report and review of the literature

Abstract: Muenke is a fibroblast growth factor receptor 3 (FGFR-3)-associated syndrome, which was first described in late 1990 s. Muenke syndrome is an autosomal dominant disorder characterized mainly by coronal suture craniosynostosis, hearing impairment and intellectual disability. The syndrome is defined molecularly by a unique point mutation c.749C > G in exon 7 of the FGFR3 gene which results to an amino acid substitution p.Pro250Arg of the protein product. Despite the fact that the mutation rate at this nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Due to variable expressivity and incomplete penetrance, the presentation of MS ranges from a complete absence of clinical signs to severe and life-threatening consequences of defective skull growth, such as craniosynostosis, hearing loss, and increased intracranial pressure [6]. Furthermore, many MS traits have considerable overlap with other craniosynostosis syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to variable expressivity and incomplete penetrance, the presentation of MS ranges from a complete absence of clinical signs to severe and life-threatening consequences of defective skull growth, such as craniosynostosis, hearing loss, and increased intracranial pressure [6]. Furthermore, many MS traits have considerable overlap with other craniosynostosis syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by incomplete penetrance and variable expressivity [3], MS is a rare and complex disease that remains an immense challenge to study, diagnose, and treat. Several studies have documented the qualitative clinical phenotype of MS, which includes, but is not limited to, uni-or bilateral premature fusion of one or more cranial sutures (craniosynostosis), macrocephaly without craniosynostosis, dysmorphic craniofacial features, dental malocclusion, midfacial hypoplasia, and a high arch palate [4][5][6][7][8][9][10][11][12]. However, to date, very few quantitative craniofacial morphology studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MS is an autosomal dominant disorder characterized by coronal suture CS. MS in the association with an identical gene mutation, an unique point mutation c.749C > G in exon 7 of the FGFR3 gene involved with MS.[ 15 ] Sagittal CS: Sagittal CS is the most common form of CS found in India. Children were the affected group, approximately one in every 5,000 newborn.…”
Section: F Ibroblast G Rowth F mentioning
confidence: 99%
“…8). 71,72 Another mutation, A391E (p.Ala391Glu), is associated with the crouzono-dermo-skeletal syndrome. This is a phenocopy of Crouzon syndrome in association with acanthosis nigricans.…”
Section: Fgfr-related Syndromesmentioning
confidence: 99%